A unified approach for mix design of concrete containing supplementary cementitious materials based on reactivity moduli. (1st December 2018) - Xie, T.; Visintin, P.
Abstract: A growing awareness of the environmental impact of concrete production and usage has resulted in an expansion in the use of supplementary cementitious materials (SCMs) in ordinary Portland cement (OPC) based concrete. Research has produced a significant number of mix designs based on a large range of SCMs at different replacement ratios. Significantly, the results of each study are not always transferable, as unlike OPC which is generally highly controlled chemically, SCMs of a given type are generally characterised by a broad chemical makeup. In this study, the fundamental chemical and mineralogical compositions of wide-range of cementitious materials are inspected and the critical elements (i.e. oxides) are identified. The hydraulic activity of individual and blended binders are assessed and quantified based on the oxides identified leading to the quantification of a reactivity index. It is then shown how the reactivity index can be used as the basis of mix design for unitary and blended binders containing a wide range of SCM types and replacement ratios.